Euripide fra ‘tradizione’ e ‘rivoluzione’: un dibattito (ri)aperto - Andrea Rodighiero (Annali Online dell'Università di Ferrara. Sezione Lettere, 2017)
Discussion and analysis of P. Pucci’s Euripides’s Revolution under Cover (2016), with a short paragraph on M. Lefkowitz’s Euripides and the Gods (2016). The paper focuses on some passages of the Euripidean drama, where abstract and non-anthropomorphic forms and values, playing the same function, replace the Olympian gods, and briefly investigates the consequences (and the models) of that disembodiment.